Attitudes towards seclusion and restraint in mental health settings: findings from a large, community-based survey of consumers, carers and mental health professionals. (12th August 2016) - Kinner, S. A.; Harvey, C.; Hamilton, B.; Brophy, L.; Roper, C.; McSherry, B.; Young, J. T.
Abstract : Aims: There are growing calls to reduce, and where possible eliminate, the use of seclusion and restraint in mental health settings, but the attitudes and beliefs of consumers, carers and mental health professionals towards these practices are not well understood. The aim of this study was to compare the attitudes of mental health service consumers, carers and mental health professionals towards seclusion and restraint in mental health settings. In particular, it aimed to explore beliefs regarding whether elimination of seclusion and restraint was desirable and possible. Methods: In 2014, an online survey was developed and widely advertised in Australia via the National Mental Health Commission and through mental health networks. The survey adopted a mixed-methods design, including both quantitative and qualitative questions concerning participants' demographic details, the use of seclusion and restraint in practice and their views on strategies for reducing and eliminating these practices. Results: In total 1150 survey responses were analysed. A large majority of participants believed that seclusion and restraint practices were likely to cause harm, breach human rights, compromise trust and potentially cause or trigger past trauma. Consumers were more likely than professionals to view these practices as harmful. The vast majority of participants believed that it was both desirable and feasible to eliminate mechanical restraint. Many participants, particularly professionals, believed that seclusion and some forms of restraint were likely to produce some benefits, including increasing consumer safety, increasing the safety of staff and others and setting behavioural boundaries. Conclusions: There was strong agreement across participant groups that the use of seclusion and restraint is harmful, breaches human rights and compromises the therapeutic relationship and trust between mental health service providers and those who experience these restrictive practices. However, some benefits were also identified, particularly by professionals. Participants had mixed views regarding the feasibility and desirability of eliminating these practices.